Anthelmintic Potential of Annona muricata seed Infusion: An In Vitro Study on Haemonchus contortus in Goats - Baihaqi, Zein Ahmad; Lisnanti, Ertika Fitri; Tamara, Safira; Ekawasti, Fitrine; Anggrahini, Santika; Fauziah, Ima (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Parasitic infections, particularly those caused by Haemonchus contortus, significantly impact the health and productivity of small ruminants worldwide. Traditional anthelmintic treatments are increasingly challenged by resistance issues, prompting the search for alternative treatments. The objective of this study was to assess the effectiveness of Annona muricata seed infusion on Haemonchus contortus mortality in goats in vitro. The research was conducted from November 2023 to March 2024 at the Laboratory of the Faculty of Agriculture, Islamic University of Kadiri, and BRIN. The method employed was one-way ANOVA. Treatments included a negative control with 0.9% NaCl, 10% concentration infusion, 20% concentration infusion, and albendazole. Mortality rates were assessed at 0.5, 1, 2, 4, 6, 8, 10, and 12-hour intervals. The results revealed that Annona muricata seed infusion contains compounds such as tannins, flavonoids, alkaloids, saponins, and steroids, which are capable of damaging the cuticle and buccal tissues of Haemonchus contortus. Phenolic content was measured at total phenolics of 9.1 mg RE / g Dw, total flavonoids of 4.7 mg RE / g Dw, total tannins of 7.2%, condensed tannins / CT of 3.4%, and hydrolyzable tannins / HT of 3.9%. Infusions at 10% and 20% concentrations achieved 100% mortality of Haemonchus contortus by the 8th hour. Scanning Electron Microscopy (SEM) revealed structural changes in Haemonchus contortus at different infusion concentrations, including wrinkling, irregular lines, and the presence of holes in the cuticle and buccal regions. The infusion of Annona muricata seed infusion is effective as an anthelmintic against Haemonchus contortus, achieving 100% mortality at concentrations of 10% and 20% within 8 hours. The study also demonstrates structural damage to the worms, affirming the potential of Pineapple Peel infusion as a natural parasitic control in small ruminants.